Effect of Early Feeding on Intestinal Permeability and Inflammation Markers in Infants with Genetic Susceptibility to Type 1 Diabetes: A Randomized Clinical Trial - Siljander Heli; Jason Eeva; Ruohtula Terhi; Selvenius Jenni; Koivusaari Katariina; Salonen Marja; Ahonen Suvi; Honkanen Jarno; Ilonen Jorma; Vaarala Outi; Virtanen Suvi M.; Lähdeaho Marja-Leena; et al. (Mosby Inc., 2022)
Objectives
To assess whether weaning to an extensively hydrolyzed formula (EHF) decreases gut permeability and/or markers of intestinal inflammation in infants with HLA-conferred diabetes susceptibility, when compared with conventional formula.
Study design
By analyzing 1468 expecting biological parent pairs for HLA-conferred susceptibility for type 1 diabetes, 465 couples (32 %) potentially eligible for the study were identified. After further parental consent, 332 babies to be born were randomized at 35th gestational week. HLA genotyping was performed at birth in 309 infants. Out of 87 eligible children, 73 infants participated in the intervention study: 33 in the EHF group and 40 in the control group. Clinical visits took place at 3, 6, 9, and 12 months of age. The infants were provided either EHF or conventional formula whenever breastfeeding was not available or additional feeding was required over the first 9 months of life. The main outcome was the lactulose to mannitol ratio (L/M ratio) at 9 months. The secondary outcomes were L/M ratio at 3, 6, and 12 months of age, and fecal calprotectin and human beta-defensin 2 (HBD-2) levels at each visit.
Results
Compared with controls, the median L/M ratio was lower in the EHF group at 9 months (.006 vs .028; P = .005). Otherwise, the levels of intestinal permeability, fecal calprotectin, and HBD-2 were comparable between the two groups, although slight differences in the age-related dynamics of these markers were observed.
Conclusions
It is possible to decrease intestinal permeability in infancy through weaning to an extensively hydrolyzed formula. This may reduce the early exposure to dietary antigens.
Trial registration
Clinicaltrials.gov: NCT01735123.
Abbreviations
EHFExtensively hydrolyzed formula; IDDMInsulin dependent diabetes mellitus; HBD-2Human beta-defensin 2; L/MLactulose/mannitol; T1DType 1 diabetes